ENHANCING VOCABULARY MASTERY AND RETENTION AMONG GRADE EIGHT STUDENTS IN A RURAL SETTING THROUGH SPOTIFY INTEGRATION: A CLASSROOM ACTION RESEARCH STUDY - BADHE, BERNADETHA; URAN, STEFANUS IGOLOIS GRENGA; MUKE, EFEMIA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This classroom action research examines using sportify as a digital platform to enhance vocabulary mastery and retention among Grade Eight students in rural settings. Conducted at SMP Yapenthom 1 Maumere during the 2024-2025 academic year, the study employed a mixed-method approach, incorporating qualitative and quantitative data collection through observations, questionnaires, interviews, and vocabulary tests. The interaction was implemented in two cycles using the Kemmis and McTaggart action research model. Findings revealed significant improvements in student's vocabulary retention and comprehension, with mean scores of 90.65 in reading and 94.45 in listening skills after the second cycle. Students demonstrated heightened engagement and positively perceived sportify as a learning tool. This study highlights the potential of integrating technology to address educational challenges in rural contexts and provides practical implications for fostering effective and interactive language learning environments. ABSTRAK Penelitian tindakan kelas ini meneliti penggunaan sportify sebagai platform digital untuk meningkatkan penguasaan dan retensi kosakata di antara siswa Kelas Delapan di daerah pedesaan. Dilaksanakan di SMP Yapenthom 1 Maumere selama tahun ajaran 2024-2025, penelitian ini menggunakan pendekatan metode campuran, menggabungkan pengumpulan data kualitatif dan kuantitatif melalui observasi, kuesioner, wawancara, dan tes kosakata. Interaksi dilaksanakan dalam dua siklus menggunakan model penelitian tindakan Kemmis dan McTaggart. Temuan penelitian mengungkapkan peningkatan signifikan dalam retensi dan pemahaman kosakata siswa, dengan skor rata-rata 90,65 dalam keterampilan membaca dan 94,45 dalam keterampilan mendengarkan setelah siklus kedua. Siswa menunjukkan peningkatan keterlibatan dan secara positif menganggap sportify sebagai alat pembelajaran. Penelitian ini menyoroti potensi integrasi teknologi untuk mengatasi tantangan pendidikan dalam konteks pedesaan dan memberikan implikasi praktis untuk membina lingkungan belajar bahasa yang efektif dan interaktif.